2021
DOI: 10.1371/journal.pone.0254244
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on Physical Activity of Czech children

Abstract: Introduction The pandemic of coronavirus disease (COVID-19) and related restrictions (closed schools and sports centers, social isolation, masks) may have a negative impact on children’s health. The purpose of this study was to evaluate the level of physical activity (PA) of Czech children during COVID-19 in autumn 2020. Methods Ninety-eight Czech children (mean age = 10.1 ± 1.47 years) completed the standardized Physical Activity Questionnaire for Older Czech Children (PAQ-C/cz) during COVID lockdown. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
2
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 62 publications
4
42
2
4
Order By: Relevance
“…Programmatic strategies using these methods are required to promote physical activity among school-aged children to reduce the risk of poor balance and an associated increase in the number of falls during periods when there are restrictions on movement outside the home due to the pandemic. However, our findings are not similar to those of previous studies [22][23][24][25] that demonstrated a significant decrease in physical activity in children after the emergency declaration compared to that in children before the emergency declaration. In the present study, the total time of physical activity increased among children in Japan, which is in line with the results of studies from Belgium, the Czech Republic, Germany, and Spain [26][27][28][29].…”
Section: Discussioncontrasting
confidence: 99%
“…Programmatic strategies using these methods are required to promote physical activity among school-aged children to reduce the risk of poor balance and an associated increase in the number of falls during periods when there are restrictions on movement outside the home due to the pandemic. However, our findings are not similar to those of previous studies [22][23][24][25] that demonstrated a significant decrease in physical activity in children after the emergency declaration compared to that in children before the emergency declaration. In the present study, the total time of physical activity increased among children in Japan, which is in line with the results of studies from Belgium, the Czech Republic, Germany, and Spain [26][27][28][29].…”
Section: Discussioncontrasting
confidence: 99%
“…Although we found no between-group difference in weight change, one-third of adolescents in the TLE groups and one-quarter of the control group achieved clinically meaningful weight loss of more than 5% of their baseline weight. One possible explanation for the absence of between-group difference lies in the structured day hypothesis [56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…The research conducted before the pandemic revealed that adolescents declaring a higher physical activity level at the same time have better nutritional behaviors than the other adolescents [29]. Moreover, during the COVID-19 pandemic the physical activity level in this group has significantly decreased, associated with lack of physical education lessons at school, but also with closed playgrounds and courts [28,71,72] being indicated by adolescents as a reason of their reduced physical activity [27]. This problem may have existed in the studied population and may have caused that only adolescents of the highest motivation had an adequate physical activity level, as they were seeking alternative options to practicing sports.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, the COVID-19 pandemic reduced for children and adolescents the possibilities of physical activity and team sports' practicing, due to remote learning systems as well as closed playgrounds and courts, which caused, in a number of studies, a reduced physical activity level in this population group [25][26][27][28]. However, in a number of studies conducted in a population of adolescents, while sport activities were decreased, habitual physical activities and outdoor activities, such as gardening, housework, cycling, skiing, or walking, were increased [29,30].…”
Section: Introductionmentioning
confidence: 99%